Glutamic Acid Decarboxylase 1 Gene Methylation and Panic Disorder Severity: Making the Connection by Brain Gray Matter Volume - Wu, Huiqin; Zhong, Yuan; Xu, Huazhen; Ding, Huachen; Yuan, Shiting; Wu, Yun; Liu, Gang; Liu, Na; Wang, Chun (Frontiers in Psychiatry, 2022)
Objective: This study aimed to test the hypothesis that the relationship between glutamic acid decarboxylase (GAD) 1 gene methylation and severity of clinical symptoms of panic disorder (PD) is mediated by the effect of GAD1 gene methylation on gray matter volume (GMV) and the effect of GMV on PD. Methods: PD (n=24) patients were recruited consecutively from the Affiliated Brain Hospital of Nanjing Medical University through outpatient and public advertising, eligible healthy controls (HCs) (n=22) were recruited from public advertising. We compared GMV and GAD1 gene methylation in PD and HCs to estimate the differences, and on the basis of the relationship between GMV and GAD1 gene methylation in PD patients was evaluated, the role of GMV as a mediator of GAD1 gene methylation and PD clinical symptoms was analyzed. Results: Average methylation across Cytosine-phosphate-guanine (CPG) 7 island of GAD1 gene promoter was significantly lower in patients compared to HCs (P = 0.02). Pearson correlation analysis found a significant negative association between cg171674146 (cg12) site and clinical severity (n=24, r=-0.456, p=0.025). Compared to HCs, patients with PD had decreased GMV in several brain regions, which were also associated with PD severity. Left postcentral gyrus (PoCG) GMV mediated the association between cg12 methylation and PD severity, and there was a significant mediation effect of right angular gyrus (ANG) GMV on the relationship between cg12 methylation and PD severity. Limitation: No direct conclusions regarding the respective methylation patterns in brain tissue can be drawn; the study is cross-sectional; relatively small size